At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
[tex]h^{-1}(x) = \frac{4}{3}x + \frac{23}{3}[/tex]
Step-by-step explanation:
Given
Graph h:
[tex](x_1,y_1) = (1,-5)[/tex]
[tex](x_2,y_2) = (9,1)[/tex]
Required
Plot [tex]h^{-1}(x)[/tex]
First, calculate h(x)
Calculate slope (m)
[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
[tex]m = \frac{1--5}{9-1}[/tex]
[tex]m = \frac{6}{8}[/tex]
[tex]m = \frac{3}{4}[/tex]
The equation is:
[tex]y = m(x - x_1) + y_1[/tex]
So, we have:
[tex]y = \frac{3}{4}(x - 1) -5[/tex]
[tex]y = \frac{3}{4}x - \frac{3}{4} -5[/tex]
[tex]y = \frac{3}{4}x + \frac{-3 - 20}{4}[/tex]
[tex]y = \frac{3}{4}x - \frac{23}{4}[/tex]
Next, calculate [tex]h^{-1}(x)[/tex]
Swap y and x
[tex]x = \frac{3}{4}y - \frac{23}{4}[/tex]
Solve for y
[tex]\frac{3}{4}y = x + \frac{23}{4}[/tex]
Multiply through by 4
[tex]3y = 4x + 23[/tex]
Divide through by 3
[tex]y = \frac{4}{3}x + \frac{23}{3}[/tex]
Replace y with [tex]h^{-1}(x)[/tex]
[tex]h^{-1}(x) = \frac{4}{3}x + \frac{23}{3}[/tex]
See attachment for graph
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.